-9x-18y=36

Simple and best practice solution for -9x-18y=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9x-18y=36 equation:


Simplifying
-9x + -18y = 36

Solving
-9x + -18y = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18y' to each side of the equation.
-9x + -18y + 18y = 36 + 18y

Combine like terms: -18y + 18y = 0
-9x + 0 = 36 + 18y
-9x = 36 + 18y

Divide each side by '-9'.
x = -4 + -2y

Simplifying
x = -4 + -2y

See similar equations:

| 3(-6)-y=-17 | | -20+-4x=-2(4x+-4) | | 5000=-p^2+120p+1400 | | p(0)=2.5p(1) | | 2x+40=2/11x | | 3n+6=210 | | 2(2x+1)+2(3x+3)=78 | | -16x^2-150x+250=0 | | 2/5+1/3= | | 3p=2p+72 | | 5a(a-3)-7(a-3)=0 | | 10x+10y=200 | | -4+6y=-12 | | 20.1=24.6+a(17.02) | | 4(3+2m)-6(-8x-3)= | | 1/2d-3=2 | | g-4g=-5 | | 20-k=9 | | (5x-20)=(4x) | | x=sqrt(4x+12) | | 0.3(x+20)-0.02(x-10)=-2.2 | | 20-k= | | f(x)=ln(8) | | 28x^2=3x+1 | | -(f+5)=-14 | | 10x-y=-23 | | f(x)=-x^2+3x+18 | | 5x-16=14-5y | | 21+x=13 | | 5.3+U=3.20-2.7 | | x+y+3z=13 | | 7n^2+22n+5=0 |

Equations solver categories